2015
DOI: 10.1016/j.livsci.2015.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Breeding programs for dairy goats generate profits in Brazil

Abstract: a b s t r a c tThis work aims to evaluate the economic feasibility of a breeding program for dairy goats in developing countries. A traditional scheme was compared with a scheme using a progeny test. In the traditional scheme, farm records are used and the selection of bucks is based on reproduction and milk yield of their dams, while the selection of does is based on their own performance and on their dam's performance. Analyses were performed using the ZPLAN software, which uses a deterministic approach to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
2
4
3
Order By: Relevance
“…The basic descriptive statistics for Florida and Payoya female fertility traits are presented in Table 1. The AgFiKid ranged between 12 and 24.6 months in Florida and 12 and 33 months in Payoya, with an average of 15.98 months ± 2.85 and 18.93 months ± 4.83 for Florida and Payoya, respectively, and was within the range of the values reported by other authors in US dairy goats [21,22] and Mexican Saanen goat [23], higher than those observed in Polish and Norwegian [24] and Brazilian dairy goat [25], and lower than that for the Toggenburg breed [26]. The more intensive production system (Florida) reduced AgFiKid by 88.5 days in comparison with the extensive system (Payoya).…”
Section: Phenotypic Parameters Of Fertility Traitssupporting
confidence: 82%
See 1 more Smart Citation
“…The basic descriptive statistics for Florida and Payoya female fertility traits are presented in Table 1. The AgFiKid ranged between 12 and 24.6 months in Florida and 12 and 33 months in Payoya, with an average of 15.98 months ± 2.85 and 18.93 months ± 4.83 for Florida and Payoya, respectively, and was within the range of the values reported by other authors in US dairy goats [21,22] and Mexican Saanen goat [23], higher than those observed in Polish and Norwegian [24] and Brazilian dairy goat [25], and lower than that for the Toggenburg breed [26]. The more intensive production system (Florida) reduced AgFiKid by 88.5 days in comparison with the extensive system (Payoya).…”
Section: Phenotypic Parameters Of Fertility Traitssupporting
confidence: 82%
“…The values for Int12Kid, Int3toKid, and IntAllKid were similar in both breeds and ranged between 5.7and 17.1 months in Florida and 6.3 and 16.7 months in Payoya. Their averages varied from 10.78 months ± 1.74 (for Int12Kid in Payoya) to 11.46 months ± 1.72 (for Int3toKid in Payoya) and were lower than the ones mentioned in US dairy goats [7,19,20], but higher than the values obtained in Toggenburg [26] and Brazilian goats [25]. The coefficients of variation oscillated between 16.8% and 18.2% (for Int3toKid and Int12Kid, respectively) in Florida and 15.0 and 25.5% (for Int3toKid and AgFiKid, respectively) in Payoya.…”
Section: Phenotypic Parameters Of Fertility Traitscontrasting
confidence: 54%
“…These costs alone justify the importance of evaluating the programme's profitability. The annual fixed costs of an animal breeding programme in Brazil have been estimated at US$ 38 thousand to US$ 150 thousand (Lôbo, Penna, & Madalena, and Lôbo, Madalena, & Penna, for dual‐purpose cattle; Santos, Lôbo, Facó, Gonçalves, & Lôbo, for dairy goats). These costs represented approximately US$ 0.79/year to US$ 1.07/year per female evaluated.…”
Section: Investment In Breeding Programmesmentioning
confidence: 99%
“…This activity involves the collection of information regarding the traits of the selection criteria and is the one that has the highest costs in a breeding programme, since each measurement is a variable cost, which will increase as more animals are evaluated. The average variable costs per head/year in Brazil were estimated at US $ 2.51 to US $ 2.74 for dual‐purpose cattle (Lôbo, Madalena, et al, ; Lôbo, Penna, et al, ) and US $ 1.40 to US $ 3.56 for dairy goats (Santos et al, ), depending on the selection scheme. These costs for dairy goats were estimated according to observations based on experiences with Capragene, in its progeny testing for young bucks.…”
Section: Investment In Breeding Programmesmentioning
confidence: 99%
See 1 more Smart Citation